Strengthening Biomedical Research in Yemen: A Pressing Need for Raising Research Funding - Rashad Abdul-Ghani (University of Science and Technology, Sana’a, Yemen, 2024)
This editorial emphasizes the need to secure funding for biomedical research in Yemen, considering the ongoing challenges faced by the research community in the country due to the war and humanitarian crises in the recent years and the lack of domestic research funding. It raises some issues related to improving the fundraising capacity of research institutions and highlights the success story of the University of Science and Technology in Sana’a in raising international funding for research projects on infectious diseases over the past decade.